FENOMENA PERUBAHAN PEMANFAATAN RUANG DAN PERTUMBUHAN AKTIVITAS PERKOTAAN (Kasus Koridor Ruas Jalan Hertasning - Samata di Makassar - Gowa) - Sakti, Harry Hardian (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2016)
The accelerations of Hertasning area development within Metropolitan Mamminasata zone, identified as a result of spatial physical change factors and the existence of Hertasning-Samata road corridor connecting Makassar city and Gowa Regency. This research aims to examine and analyze the determinants of spatial utilization change and influence of road corridor towards the growth of urban activities. In this research used quantitative methods with analysis tools, statistic descriptive to explain the determinants of spatial utilization change and analysis of correlation tests to explain the effects of urban activities growth. The results of analysis and discussions identified the determinant factors of spatial utilization change are movement distance, transportation infrastructures, availability of education facilities, availability of commercials and services facilities, types of land use, land prices, land sell values, site strategic values, and site selections, also factors that affected the growth of urban activities are settlement activities, commercials and services, educations, and movement network. Spatial development within Hertasning area has a significant role towards spatial utilization changes, because of structuring pattern of spatial utilizations that become basis to determine the development of spatial functions, therefore spatial pattern that formed appropriate to allotment and directions of future urban development.